EFFECT OF REAGENT VOLUME AND CONCENTRATION ON RECOVERIES OF MgO AND SO3 WITHIN SYNTHETIC DOLOMITE-BASED KIESERITE - Tatang Wahyudi; Retno Damayanti (Indonesian Mining Journal, 2013)
Natural kieserite is usually used for the production of epsom salt and fertilizer. Normally, the mineral is mined from geologic marine deposits and provides a soluble source of both Mg and S for plant nutrition. However, natural kieserite cannot be found in Indonesia. The fact that this country retains a lot of dolomite deposits and such a material can be processed into synthetic kieserite by sulphatization process seems promising for fertilizer industry in Indonesia. Varying the sulfuric acid concentration between 2 and 5 N and its volume from29.50 to 94.80 ml produces the MgO in MgSO4 filtrate below the specification as stated in Indonesian National Standard (14 – 19%) though its sulfur content has satisfied the requirements. It is assumed that some MgO’s (around 1.93 – 7.12%) are still available in CaSO4 deposit. To get the optimum results, an appropriate calcula- tion is required when adding sulfuric acid to the process and the solution should be in neutral condition prior to separating MgSO4 – CaSO4 as well.